Effects of early exercise on cardiac function and lipid metabolism pathway in heart failure - de Souza, Sérgio Luiz Borges [UNESP]; Mota, Gustavo Augusto Ferreira [UNESP]; da Silva, Vitor Loureiro [UNESP]; Vileigas, Danielle Fernandes [UNESP]; Sant'Ana, Paula Grippa [UNESP]; Gregolin, Cristina Schmitt [UNESP]; Figueira, Rebeca Lopes [UNESP]; Batah, Sabrina Setembre; Fabro, Alexandre Todorovic; Murata, Gilson Masahiro; Bazan, Silmeia Garcia Zanati [UNESP]; Okoshi, Marina Politi [UNESP]; et al. (Wiley, 2023)
We employed an early training exercise program, immediately after recovery from surgery, and before severe cardiac hypertrophy, to study the underlying mechanism involved with the amelioration of cardiac dysfunction in aortic stenosis (AS) rats. As ET induces angiogenesis and oxygen support, we aimed to verify the effect of exercise on myocardial lipid metabolism disturbance. Wistar rats were divided into Sham, trained Sham (ShamT), AS and trained AS (AST). The exercise consisted of 5-week sessions of treadmill running for 16 weeks. Statistical analysis was conducted by anova or Kruskal–Wallis test and Goodman test. A global correlation between variables was also performed using a two-tailed Pearson's correlation test. AST rats displayed a higher functional capacity and a lower cardiac remodelling and dysfunction when compared to AS, as well as the myocardial capillary rarefaction was prevented. Regarding metabolic properties, immunoblotting and enzymatic assay raised beneficial effects of exercise on fatty acid transport and oxidation pathways. The correlation assessment indicated a positive correlation between variables of angiogenesis and FA utilisation, as well as between metabolism and echocardiographic parameters. In conclusion, early exercise improves exercise tolerance and attenuates cardiac structural and functional remodelling. In parallel, exercise attenuated myocardial capillary and lipid metabolism derangement in rats with aortic stenosis-induced heart failure.
Keywords: angiogenesis; aortic stenosis; fatty acid oxidation; physical exercise; pressure overload; SIRT1